Faktor-Faktor Yang Mempengaruhi Pengambilan Keputusan Pembelian Mobil Di Pedesaan - Clarissa Handoko; David Wardana; Gabriella Jessica; Richard Raphita (Indonesian Business Review, 2019)
Ministry of Industry, in collaboration with PT Velasto Indonesia, has produced village vehicle prototype to support village mass transportation program. But, factors affecting potential village vehicle buyers’ decision in buying the product has not been studied. To solve the problem, Analytic Hierarchy Process (AHP) is used to determine rankings of importance of factors affecting village vehicle purchasing decision. Based on AHP analysis, it is concluded that price, flexibility and performance are three most important factors in village vehicle purchasing decision. As for village vehicle producer, AHP result is helpful to test the prototype’s compatibility with its future user.